Synergic removal of p-chloronitrobenzene by reduced graphene oxide/BiOBr/TiO2 nanotube arrays photoelectrocatalysis coupled biodegradation: Performance and microbial response. (October 2022) - Ma, Bingrui; Xin, Shuaishuai; Liu, Wenjie; She, Zonglian; Zhao, Yangguo; Guo, Liang; Jin, Chunji; Ji, Junyuan; Gao, Mengchun
Abstract: The coupled photoelectrocatalytic and biodegradation of p -chloronitrobenzene ( p -CNB) was developed with the reduced graphene oxide/BiOBr/TiO2 nanotube arrays (GB/TNAs) as the photoelectrodes. The p -CNB removal performance, microbial activity and microbial community were systematically investigated in different bioreactors. The photoelectrocatalytic degradation improved the biodegradability of p -CNB. Compared to single biodegradation, the coupled degradation process exhibited higher p -CNB removal and mineralization efficiency. The specific oxygen utilization rate and dehydrogenase activity in single biodegradation bioreactor declined by 48.63 % and 41.14 % on day 25, indicating that p -CNB inhibited the microbial metabolic activity. However, the photoelectrocatalytic degradation could effectively reduce the inhibition of p -CNB on microbial activity of bioreactors. The variations of microbial reactive oxygen species production, antioxidant enzyme activity, and lactate dehydrogenase release confirmed that photoelectrocatalytic degradation declined the biotoxicity of p -CNB to the microorganisms in the coupled degradation process. p -CNB reduced the microbial richness and diversity in the single biodegradation process, whereas they increased obviously with the increase of photoelectrocatalytic degradation time in the combined degradation process. Highlights: The photoelectrocatalytic degradation improved the biodegradability of p -CNB. The coupled photoelectrocatalytic and biodegradation achieved higher p -CNB removal. The photoelectrocatalytic degradation declined the biotoxicity of p -CNB. The photoelectrocatalytic degradation reduced p -CNB inhibition to microbial richness.